Comparative Mitogenomic Analyses of Psectrocladius (Diptera: Chironomidae) - Xue-Yao Chen; Xiu-Ru Xiao; Yan Zhang; Zhi-Chao Zhang; Dong-Sheng Zhang; Zheng Liu; Xiao-Long Lin (Insects)
Psectrocladius, a genus within the species-rich subfamily Orthocladiinae (Diptera: Chironomidae), remains poorly resolved in molecular phylogenetics due to limited available molecular data. Here, we sequenced and analyzed the complete mitogenomes of five Psectrocladius species, using two Rheocricotopus species as outgroups. Our results reveal that the mitogenomes of Psectrocladius are structurally conserved and retain a presumed ancestral gene order. The nucleotide composition of these newly generated mitogenomes exhibits a pronounced A + T bias, which is characteristic of typical insect mitogenomes. The substitution rates, estimated using Ka/Ks ratios, indicate that all protein-coding genes are under purifying selection. The strongest purifying selection pressure was observed in the CO1 gene, while the weakest was in the ND5 gene. Both the maximum likelihood and Bayesian inference trees consistently show the following topology: ((((P. schlienzi + P. bisetus) + P. barbimanus) + P. oligosetus) + P. aquatronus). This study provides key insights into chironomid mitogenomes and their gene properties, offering valuable reference data for future research.